2022
DOI: 10.1073/pnas.2115017119
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone exerts biphasic control of regenerative signaling, coordinating the completion of regeneration with developmental progression

Abstract: In Drosophila melanogaster, loss of regenerative capacity in wing imaginal discs coincides with an increase in systemic levels of the steroid hormone ecdysone, a key coordinator of their developmental progression. Regenerating discs release the relaxin hormone Dilp8 (Drosophila insulin-like peptide 8) to limit ecdysone synthesis and extend the regenerative period. Here, we describe how regenerating tissues produce a biphasic response to ecdysone levels: lower concentrations of ecdysone promote local and system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…How Ec is concentrated locally in these two scenarios is unclear, but could rely on secretion, uptake, or local sequestration, perhaps including low levels of Ec produced by the PG during the developmental pause. EcR activity has also been shown to be induced within larval wing discs damaged by exposure to gamma irradiation (Karanja et al, 2022), which parallels the effect of rn>rpr ts and egr ts observed in this study. However, the source of Ec following irradiation was not examined.…”
Section: The Regeneration Genes Upd3 and Ets21c Respond To Ecsupporting
confidence: 87%
See 2 more Smart Citations
“…How Ec is concentrated locally in these two scenarios is unclear, but could rely on secretion, uptake, or local sequestration, perhaps including low levels of Ec produced by the PG during the developmental pause. EcR activity has also been shown to be induced within larval wing discs damaged by exposure to gamma irradiation (Karanja et al, 2022), which parallels the effect of rn>rpr ts and egr ts observed in this study. However, the source of Ec following irradiation was not examined.…”
Section: The Regeneration Genes Upd3 and Ets21c Respond To Ecsupporting
confidence: 87%
“…Given the pro-growth Ec role in discs (Dye et al, 2017, Herboso et al, 2015, Karanja et al, 2022, Gokhale et al, 2016, Nogueira Alves et al, 2022), we assessed effects of pthm KD and Cyp18a1 KD on cell division within the blastema, focusing on R48 when 7xEcRE-GFP activity is most dependent on pthm (see Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, along with others (11, 22), strongly indicate that the regenerative capacity of damaged wing larval cells is contingent upon an environment lacking Br, thereby sustaining wing cells in a differentiation-refractory state. Indeed, it has been demonstrated that the wg 1 enhancer is activated in wing disc cells upon tissue injury, contributing to wing regeneration (25, 37), and further, this enhancer is repressed by Br in a context of tissue damage (38).…”
Section: Discussionmentioning
confidence: 99%
“…Lgr3 is also required in the PG itself for regulating ecdysone production during regeneration [ 56 ]. Notably, the lower concentrations of ecdysone, suppressed by Dilp8, effectively promote regenerative activity in damaged imaginal disks, whereas higher concentrations suppress regeneration [ 57 ] ( Figure 1a ). This peripheral tissue-CNS interaction is a typical mechanism to ensure developmental robustness in multicellular organisms, as it secures enough time for regenerating damaged imaginal disks before pupariation.…”
Section: Peripherally Derived Peptide Hormones: Ecdysone Biosynthesismentioning
confidence: 99%